Internalisasi nilai Pancasila sebagai upaya pembentukan civic disposition mahasiswa di era globalisasi - Agus, Andi Aco (Rayhan Intermedia, 2025)
This study aims to determine the process of internalizing Pancasila values in higher education institutions, the internalization of Pancasila values in shaping students' civic disposition, the challenges and opportunities for internalizing Pancasila values in the era of globalization, and effective strategies for enhancing the internalization of Pancasila among students. The research method used is descriptive research with a literature review (library research). The research activities were carried out by collecting information and data with the help of various available materials. The results of the study show that internalization of values means a process of appreciation so that these values become part of the personality structure and are manifested in concrete actions. The strategy for internalizing Pancasila values in higher education institutions is through a curricular approach, namely through compulsory general courses such as Pancasila Education and Civic Education, which include affective, cognitive, and psychomotor learning outcomes